The The Effect of Credit on Female-headed Households Welfare in Indonesia - Juwita, Gita Hayu Padma (Pusat Studi Wanita dan Keluarga UGM, 2024)
This study analyses credit's effect on female-headed household welfare in Indonesia. This paper employed a dataset from the National Socio-economic Survey (SUSENAS) conducted in 2018, which contains approximately 45,000 observations of female-headed households in Indonesia. Welfare here is measured by expenditure per capita per month of the households. This study employed Propensity Score Matching to analyse the average effect of credit to expenditure while controlling confounding factors such as age, education, location, housing status, marriage status, housewife status, employment status, and household size. The result shows that the credit extension significantly affects the expenditure of female-headed households.